The Effect of Coworker Support and Work Environment on Turnover Intention Through Work Motivation in Gen Y and Z Workers in Malang City - Gimnatyar Ganda Wijaya; Ryan Basith Fasih Khan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Coworker Support and Work Environment on Turnover Intention by mediating Work Motivation among Generation Y and Z workers in Malang City. The research uses quantitative techniques. The total population in this study was 452,435 people. The sampling technique in this study used the Hair et al. formula nx5, so 160 respondents were obtained. This study uses the Partial Least Square (PLS) data analysis method using Smart- PLS software version 3.0. The results showed that Coworker support has no effect on turnover intention, the work environment has a positive and significant impact on turnover intention, coworker support has a positive and significant effect on work motivation, the work environment has no impact on work motivation, work motivation can mediate the relationship between coworker support and turnover intention, and work motivation is not able to mediate the relationship between work environment and turnover intention in gen y and z workers in Malang City.